Rancang Bangun Sarana Konseling Pada Sekolah SMA Negeri 1 Kampung Rakyat Menggunakan PHP - Lestari Nababan, Vidya Ade (Universitas Labuhanbatu, 2021)
Counselors at the guidance and counseling institutions in schools play a role in the process of forming the personality of students and direct students to be better in honing students' abilities in the academic field. This role can be effective if guidance and counseling is supported by the existence of a good computerized system in schools, so that the processing and storage of data in counseling guidance activities can run smoothly. Therefore, in this study an information system was designed to handle the processes contained in counseling guidance including student data processing, parent data, class data, student attendance, student achievement, student cases (violations, delays, return, mutations ), and student counseling. From the information system design, a web-based guidance counseling information system was built and using the PHP Framework Codelgniter. Research from this information system produces a counseling guidance information system that can be used by BK teachers in managing the process of counseling guidance activities in SMA Negeri 1 Kampung Rakyat such as managing student data, student absences, student cases, and student counseling and can be used by students in conducting guidance for BK Teachers.